2017 թ. ՀՀ խորհրդարանական ընտրությունները. համեմատական վերլուծություն - Ալեքսանյան Արուսյակ (YSU Journal of International Affairs, 2017)
The study of the problem of party system formation and of the political parties’ role under the conditions of the development of parliamentarism in Armenia has significant meaning. Political parties, representing the interests of social groups and citizens, are the most important linkage in the political system of society. In the article, the latest changes to the Electoral Code, regarding the electoral system and the composition of the National Assembly of the Republic of Armenia are presented. The author studies the aspects of political parties of Armenia through the correlation analysis. Based on the data of the elections to the National Assembly of Armenia in 2017, the differences and similarities of the party electorates are analyzed, and a comparative analysis is given.